A descriptive survey on pet-friendly design guidelines for residential interiors - Bautista, Celine Consuelo Chongco (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study was a descriptive survey on pet-friendly design guidelines for residential interiors. The study aimed to determine the opinions of pet owners regarding the consideration of pets in interior design, assessing whether pet owners are potential clients for interior designers. The objective of the study was to determine basic guidelines for the design of pet-friendly spaces. The descriptive method of research was applied for this study. The respondents were chosen using a non-probability, purposive sampling method, selecting only dog owners, either male or female, residing within Metro Manila. The data was gathered through structured, individual interviews, conducted over a period of two weeks. The data was analyzed both qualitatively and quantitatively. The study determined that the relationships that pet owners share with their pet dog are greatly inclined towards companionship, with the owners treating the pet as they would a member of the family. Pet owners agree that interior designers should be capable of designing pet-friendly environments. The results of the study suggest that the factors to consider when creating petfriendly spaces are the following; (1) safety for both animal and human users, (2) health / hygiene, including maintenance of the space, (3) measures to control animal behavior, (4) preventing damage to possessions, and (5) considering dog characteristics, such as breed and age. The study recommends that further research be conducted with a larger sample; or to include site observations to ascertain the data gathered through the interviews.